Women's access to the political sphere in Italy: when obstacles outdo opportunities. Issue 3 (2nd July 2020) - Belluati, Marinella; Piccio, Daniela R.; Sampugnaro, Rossana
ABSTRACT: This special issue focuses on the tension between the formal rules aimed at reducing the disparity between the genders in public office and the informal barriers to women's political participation. These also include the way in which media systems portray women, taking into consideration their role either in promoting equal opportunities for women or, on the contrary, in contributing to the diffusion of gender stereotypes. This article focus on the main obstacles in the way of full implementation of gender politics in Italy.